Is chlorhexidine an ideal vehicle for calcium hydroxide? - Mohammadi, Zahed; Shalavi, Sousan (Iranian Endodontic Journal, 2012)
Microorganisms play a major role in the initiation and perpetuation of pulpal and periapical disease. In order to predictably achieve a bacteria-free root canal system, it is necessary to use intracanal medicaments. Calcium hydroxide is the most common intracanal medicaments. It is effective against primary infections. However, its effectiveness against Enterococcus faecalis and Candida albicans is controversial. On the other hand, chlorhexidine is a potent agent against Enterococcus faecalis and Candida albicans. For this reason, it has been combination of calcium hydroxide and chlorhexidine has been suggested as an intracanal medicament. The purpose of this article was to a brief review antimicrobial efficacy of calcium hydroxide, chlorhexidine, and their combination.